Crosslinked dendronized polyols as a general approach to brighter and more stable fluorophores. Issue 19 (5th February 2016) - Li, Ying; Bai, Yugang; Zheng, Nan; Liu, Yang; Vincil, Gretchen A.; Pedretti, Benjamin J.; Cheng, Jianjun; Zimmerman, Steven C.
Abstract : Fluorescent, aqueous-soluble, crosslinked dendronized polyols (CDPs) are obtained through a sequential process involving ring-opening metathesis polymerization (ROMP), intra-chain ring-closing metathesis (RCM), and hydrolysis. Abstract : Fluorescent, aqueous-soluble, crosslinked dendronized polyols (CDPs) are obtained through a sequential process involving ring-opening metathesis polymerization (ROMP), intra-chain ring-closing metathesis (RCM), and hydrolysis. This general strategy improves the quantum yields (QYs), brightness, and photostability of five common fluorophores whose emission wavelengths cover 150 nm. Additionally, the availability of the polymeric fluorophore to the cytosomes opens the door to applications in bioimaging and intracellular delivery.